IMPLIKASI PERUBAHAN UNDANG–UNDANG PERPAJAKAN TERHADAP KEPUTUSAN STRATEGI LEVERAGE BAGI PERUSAHAAN YANG TERDAFTAR DI PT. BURSA EFEK JAKARTA - Sapari Sapari (EKUITAS (Jurnal Ekonomi dan Keuangan), 2008)
This  research  examines the  connection between non debt tax shield and the change of leverage, between level of effective company tax and the change of leverage, and between operation income before depreciation and the change of leverage. This research takes 17 samples of  food and beverages companies listed in Jakarta Stock Exchange from 1st  January 1994 till 31st  December 1999. And this research uses data from 1994 – 1999 for the regression analysis. Multiple regression analysis is used to test hyphothesis 1 (H1), hyphothesis 2 (H2) and hyphothesis 3 (H3). Independent variables in the regression are level of effective company tax, non debt tax shield and operation income before depreciation, whilst independent variable in the regression is leverage.The result of this research proves that (1) non debt tax shield after the amendment of 1994 tax regulation (1995 – 1999) brings positive influence to the leverage change, (2) level of effective company tax after the amendment of 1994 tax regulation (1995 – 1999) brings negative influence to the leverage change, and (3) operation income before  depreciation  after the amendment of 1994 tax regulation (1995 – 1999) brings positive influence to the leverage change.